ANALISIS UJI PERFORMA AIR CONDITIONER DAIKIN 1 HP MENGGUNAKAN REFRIGERAN R22 DENGAN MEMBANDINGKAN VARIASI BUKAAN KATUP REFRIGERAN 0,25 BUKAAN DAN 1 BUKAAN PADA VARIASI SUHU RUANGAN 18°C - 27°C : PERFORMANCE TEST ANALYSIS OF A 1 HP DAIKIN AIR CONDITIONER USING R22 REFRIGERANT BY COMPARING VARIATIONS IN REFRIGERANT VALVE OPENINGS OF 0,25 AND 1 UNDER VARIATIONS OF ROOM TEMPERATURES FROM 18°C TO 27°C - BOBBY BAGAS PRAKOSO (Jurnal Teknik Mesin, 2026)
The vapor compression refrigeration system with Air Conditioner (AC) cooling systems has continued to evolve with the advancement of time. Especially today, AC cooling systems are highly needed by humans in daily life, particularly during hot weather conditions. However, it cannot be denied that many people in Indonesia still use older types of AC units with R22 refrigerant, which is known for its high electricity consumption. To address this issue, this research analyzes the performance test of an AC unit using a Daikin brand AC with a 1HP compressor and R22 refrigerant. The study will analyze the AC's performance by calculating the Coefficient of Performance (COP) under two conditions: the refrigerant valve opened to 0.25 and fully opened, with temperature samples taken from 18°C to 27°C. The data obtained will be used to calculate the COP for each variation, and the best performance for the 1HP Daikin AC will be determined. Based on the research conducted, it was found that the best performance of the 1HP Daikin AC was achieved with the refrigerant valve fully opened at a temperature of 23°C, with a COP of 19.08. The lowest performance was observed with the refrigerant valve fully opened at a temperature of 20°C. When comparing all COP results at various temperatures, the 0.25 valve opening demonstrated better performance than the fully opened valve, with a COP difference of 1.02.